Pengaruh Varietas Beras Putih Sumatera Barat Terhadap Nilai Hematokrit Darah Mencit (Mus Musculus L. Swiss Webster) Jantan - Silvira Safitri (UNIVERSITAS NEGERI PADANG, 2017)
White rice is considered as a food have hyperglycemic, it can increase the risk of Diabetes Mellitus. Changes in blood hematocrit value is very risky for people with Diabetic. High hematocrit value increases the risk of hypertension in patients with Diabetic. Meanwhile, a low hematocrit values can lead to anemia in patients. Thus it made to reduce the risk of diabetic disease has to limit consumption of white rice. In fact, white rice glycemic response varies widely, influenced by processing, varieties, and chemical composition.West Sumatra white rice have high amylose deemed able to increase blood glucose slowly. The purpose of this research was to determine the effect of white rice varieties West Sumatra on blood hematocrit value mice (Mus musculus L. Swiss Webster) males. This research used Completely Randomized Design with 7 treatments and 4 replications. The treatment were 0,5 mL sugar solution as a control, and 0,5 mL of rice flour Bakwan, Ciredek, Cantiak Manih, Randah Putiah, Mundam and Anak Daro. Blood hematocrit value mice (Mus musculus L. Swiss Webster) males measured on day 7th and 15th. Data analyzed by ANOVA and DNMRT at significance level of 5%. The results showed white rice varieties West Sumatra affect blood hematocrit values mice (Mus musculus L. Swiss Webster) males. White rice varieties resulted the highest hematocrit values found in male mice is rice Ciredek of Solok. Meanwhile, the normal hematocrit values found in male mice were given rice Mundam of Pariaman. Rice Mundam can be consumed by people with Diabetes because it provides stable results for hematocrit value. Keywords: Rice White, Blood Glucose, Mus musculus, Hematocrit